(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
The methanolic extract of Buchholzia coriacea seeds (MEBC) has been reported to induce male reproductive toxicity by decreasing sperm parameters and fertility index. To elucidate the possible mechanism(s), the effects of graded doses of MEBC on sex hormones and sperm profile were investigated in this study. The MEBC (e.g., 50, 200, 400, and 600 mg/kg) was administered daily (p.o.) to male Wistar rats for 6 weeks, while a concurrent control group received distilled water (vehicle). Then, the animals were sacrificed under sodium pentobarbital anaesthesia. Weights of organs were recorded, and the sperm profile was determined microscopically. Testosterone, luteinizing hormone (LH), and follicle stimulating hormone (FSH) were assayed from the obtained serum using the ELISA technique. Sperm motility was significantly reduced by MEBC (i.e., 50 and 200 mg/kg), and sperm count reduced in all treated groups in a dose-dependent manner compared with that of the control. Serum testosterone, LH, and FSH decreased in treated rats. A histopathological examination of testes showed a considerable depletion and necrosis of the epithelium of seminiferous tubules. The result suggests that Buchholzia coriacea seeds induce male reproductive toxicity by suppressing the pituitary-gonadal axis.